Education Of The Future In The Conditions Of Vuca World; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 116 : International Conference on Economic and Social Trends for Sustainability of Modern Society (ICEST-II 2021) - Brylina I. V. Irina Vladimirovna; Okonskaya N. K. Natalia Kamilievna; Ermakov M. A. Mikhail Aleksandrovich; Brylin A. V. Artem Vladimirovich (2021, 2021)
Title screen